Colchicine-induced myoneuropathy in a cyclosporine-treated renal transplant recipient - Kyungmin Huh; Ji Young Joung; Hyemin Jeong; Dongmo Je; Yoon Young Cho; Hye Ryoun Jang; Wooseong Huh (The Korean Society of Nephrology, 2013)
Colchicine is a relatively safe medication that is widely used for both prevention and treatment of gout attack. However, serious adverse events, including myoneuropathy and multiorgan failure, have been reported. We report a case of colchicine-induced myoneuropathy in a female kidney transplant recipient who had been taking cyclosporine. She developed gastrointestinal discomfort and paresthesia 5 days after the initiation of colchicine. She showed signs of myoneuropathy, and hepatic and renal injury. Colchicine toxicity was suspected, and colchicine was discontinued. Her symptoms and laboratory findings improved gradually. Literature was reviewed for previous reports of colchicine-induced myoneuropathy in solid organ transplant recipients.